A Review on Evaluating the Optimization of Fibre Reinforced Polymer for Compound/Repair Clamp on Leaked Piping System using Computational Simulation - Pillai, Ragu Chanthira; Tajul Arifin, Ahmad Mubarak; Nor Salim, Nor Adrian; Rahman, Mohd Nasrull; Taib, Ishkrizat Osman; Osman, Shahrul Azmir; M. Letchumanan, Shaktivell (semarak ilmu, 2024)
Most industries around world depend on pipelines to transfer millions of gallons of flammable and non-flammable materials. However, this pipeline system has been affected by exposure, which may cause the entire system to fail due to corrosion-based issues. Repair clamps have been used to prevent total failure from happening in a continuous run. However, current design of repair clamp is consisting of metal whereby long usage on corroded pipe could be much more affected. The weight factor will be affecting the fluid flow and the structure of pipe when used in long run. Therefore, in this research, new design for the repair clamp will be done and the material will be change to fibre reinforced polymer (FRP). The new design with FRP will be undergo various stimulation on SolidWorks to compare the properties of clamp and the effect on the affected pipe. Since the FRP material properties has been proven to be more stronger and sustainable compare steel that has been using currently, it will be much more effective to use. As a result, the new design will be much more sustain than the old metal repair clamp. Since the new clamp is lightweight, the weight no longer will affect the corroded pipe internally and externally. Moreover, in this research some of the current repair clamp parts has been reduced and changed to compromise with the usage of the FRP.